Life strategies of pacific salmon. Communication 2. Formation of life-history forms. Variability in sex ratio - S. L. Marchenko (Известия ТИНРО)
Conditions determining the vector of ontogenetic development and factors influencing the sex ratio for various life-history forms of pacific salmon (gen. Oncorhynchus) are discussed on the basis of cited data.